2010
DOI: 10.3109/02841850903436659
|View full text |Cite
|
Sign up to set email alerts
|

Galactography: An application of the galactogram imaging classification system (GICS)

Abstract: The present study shows a good correlation between GICS categories and histological diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 25 publications
7
22
0
Order By: Relevance
“…Similar to other studies, the current study shows a high specificity to predict intraductal processes but no predictive value to differentiate between malignant or benign breast tumors with galactography [4,6]. Other studies suggest galactography as useful method to differentiate between malignant and benign underlying breast malignancies [7,8]. The consensus of all studies is that galactography is helpful to localize ductal abnormalities, but the reported sensitivity and specificity of galactography are within a wide range [9].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to other studies, the current study shows a high specificity to predict intraductal processes but no predictive value to differentiate between malignant or benign breast tumors with galactography [4,6]. Other studies suggest galactography as useful method to differentiate between malignant and benign underlying breast malignancies [7,8]. The consensus of all studies is that galactography is helpful to localize ductal abnormalities, but the reported sensitivity and specificity of galactography are within a wide range [9].…”
Section: Discussionsupporting
confidence: 72%
“…There are contradicting results of the potential of galactography to diagnose benign or malignant disease of the breast in patients with abnormal nipple discharge [4,[6][7][8]. The consensus of all studies is that galactography is helpful to localize ductal abnormalities, but the reported sensitivity and specificity of galactography are within a wide range [9].…”
Section: Introductionmentioning
confidence: 97%
“…Several studies [8,18,19,20] report galactographic findings suggestive of malignancy, such as ductal stenosis, multiple irregular filling defects, ductal wall irregularity, and ductal distortion. In our study, we observed a very good correlation between GICS category 5 and carcinoma, and the galactographic findings included microdefects with a moth-eaten appearance and ductal wall irregularities (fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, GL is still the subject of debate because establishing a differential diagnosis between benign and malignant lesions is considered difficult. The GICS classification system was reported recently [20], and GL has been described as a useful procedure for differentiating benign from malignant lesions. Furthermore, a recent study [22] reports that direct magnetic resonance imaging galactography may provide more diagnostic information than conventional GL in patients with PND, because it can show both ductal morphology and the extent of disease before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation